TINJAUAN YURIDIS PERJANJIAN POLA KEMITRAAN PERKEBUNAN KELAPA SAWIT INTI-PLASMA ANTARA PT. BOSWA MEGALOPOLIS DENGAN MASYARAKAT (SUATU PENELITIAN DI KABUPATEN ACEH JAYA) - MUHAMMAD MILSA (PREMISE LAW JURNAL, 2015)
Business partnership is one of business partnership patterns stipulated in PP No. 24/1997 on Partnership, in Kepmentan No. 40/kpts/OT.120/10/97, and in Permentan No. 26/Permentan/OT.140/2/2007. Although the technical requirement has been regulated, in reality, the provisions cannot accommodate all requirements in business partnership agreement between companies and the public. Partnership pattern is stipulated in Law No. 20/2008 on Micro, Small, and Medium Businesses, in PP No. 44/1997 on Partnership, in Kepmentan No. 940/kpts/OT.210/10/97 on Guidance for Partnership in Agricultural Business, and in Permentan No. 29/Permentan/OT.140/2/2007. In general, the plantation business partnership agreement between PT. Boswa Megalopolis and the people has implemented the above Kepmentan and Permentan. In practice, however, there are still many defects, especially about the content of the contract related to the mechanism of the allocation of profit, about the business partnership requirements which are not arranged in detail, and about the opportunity to make underhanded contract.The regulation of plantation business partnership has not yet provided legal certainty and legal protection for the people. It is recommended that the Government revise the substance of Kepmentan and Permentan, particularly which are related to the partnership of plant standardization and the assertion in making the contract in an authentic deed. Keywords : Judicial Review on Partnership Pattern Agreement